Color colorites and design of the interior of buildings and structures (Eurasian Scientific Herald, 2024)
Color plays a much larger role in the formation of functional processes and a favorable order for the emotional-mental state of a person. The emotional-mental state of a person requires a careful approach to the choice of harmonic harmonization of the colored gamma, taking into account the task of the interior of buildings and structures and the domestic or labor processes carried out in it, as well as aspects of the natural climatic conditions of the specific regions of construction